Dichotomies of a Gendered Science: A Brief Critical Approach to the Projects for a Feminist Science - Rubio Juan, María (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
This paper aims to show the relativistic risks involved in the successor science projects of some feminist epistemologies in terms of preserving the authority and independence that science has had until now. To this end, we briefly present the analyses of the five feminist epistemologies and how they have addressed the problem of the dichotomies present in scientific narratives and discourses, as well as a critical approach to their projects for a new science.